The Varying Effects of Uniaxial Compressive Stress on the Bainitic Transformation under Different Austenitization Temperatures - Mingxing Zhou; Guang Xu; Li Wang; Qing Yuan (Metals, 2016)
In this study, thermal simulation experiments under different austenitization temperatures and different stress states were conducted. High-temperature laser scanning confocal microscopy (LSCM), thermal dilatometry, and scanning electron microscope (SEM) were used to quantitatively investigate the effects of the uniaxial compressive stress on bainitic transformation at 330 °C following different austenitization temperatures. The transformation plasticity was also analyzed. It was found that the promotion degree of stress on bainitic transformation increases with the austenitization temperature due to larger prior austenite grain size as well as stronger promoting effect of mechanical driving force on selected variant growth at higher austenitization temperatures. The grain size and the yield strength of prior austenite are other important factors which influence the promotion degree of stress on bainitic transformation, besides the mechanical driving force provided by the stress. Moreover, the transformation plasticity increases with the austenitization temperature.